Azimuthally-variant perfect vector beams for the control of arbitrary phase and polarization ring patterns - Andrea Vogliardi; Gianluca Ruffato; Daniele Bonaldo; Simone Dal Zilio; Filippo Romanato (Light: Science & Applications)
Abstract Perfect vortices, recognized for their distinct ring profile that remains independent of the topological charge, present significant challenges in generation due to the precise control needed over both phase and polarization. In this work, we introduce and validate a new approach for generating these beams, allowing the selection of different azimuthally-variant phase gradients and vector states, thereby enabling full control over the phase and polarization patterns of perfect vortices. Using dual-functional silicon metaoptics, we achieve the compact generation of a novel class of perfect vortices, termed azimuthally-variant perfect vector beams. The optical characterization of the generated beams, performed through a filtering method, confirms their intrinsic azimuthally-variant vectorial nature. These beams exhibit unique properties that promise valuable applications in optical tweezing, the manipulation of low-refractive-index particles, the trapping of cold atoms, and high-capacity communications.